Faktor – Faktor Yang Mempengaruhi Pendapatan Nelayan Tangkap Di Desa Pagatan Besar Kecamatan Takisung Kabupaten Tanah Laut - Perdian; Suherty, Lina (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
Fishermen’s income is influenced by various factors, both internal and external factors. In this study, internal factors such as length of time at sea, operational costs, experience and total wages of crew members variable (free). In this study to determine the effect of variable length of time at sea, operational costs, experience, and the total wages of crew members on the income of fishermen in Pagatan Besar Village, Takisung District, Tanah Laut Regency. The data source used in this research is primary data in the form of interviews with a sample of 42 respondents. The analytical tool used is multiple linier regressionwith income as the dependent variable and four independent variables, namely length of fishing (days) and operational costs (Rp). Experience (years), and the total wages of the crew (Rp). Multiple linier regression will test the effect simultaneously (f test) and partially (t test) through eviews 10 software. The results of this study indicate that the length of time fishing, operational costs, and total wages of crew members individually (partially) have a significant effect on income. While the experience variable does not have a significant effect. The variables of length of time at sea, operational costs, experience, total wages of crew members together (simultaneously) have a positive effect on the income of fishermen in Pagatan Besar village, Takisung District, Tanah Laut Regency. Based on the conslusions that can be applied in order to increase fishemen’s income, where all the variables in this study can increase the income of catch fishermen in Pagatan Besar Village.